2012
DOI: 10.1107/s1744309112007129
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization and preliminary X-ray analysis of stationary phase survival protein E (SurE) fromXylella fastidiosain two crystal forms

Abstract: The bacterium Xylella fastidiosa is a phytopathogenic organism that causes citrus variegated chlorosis, a disease which attacks economically important crops, mainly oranges. In this communication, the crystallization and preliminary X-ray crystallographic analysis of XfSurE, a survival protein E from X. fastidiosa, are reported. Data were collected for two crystal forms, I and II, to 1.93 and 2.9 Å resolution, respectively. Crystal form I belonged to space group C2, with unitcell parameters a = 172.36, b = 84.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Previously, Reis et al reported crystallization conditions and data collection of two crystal forms ( Xf SurE‐DS and Xf SurE‐TB). Thus, here we describe these for the remaining two forms.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previously, Reis et al reported crystallization conditions and data collection of two crystal forms ( Xf SurE‐DS and Xf SurE‐TB). Thus, here we describe these for the remaining two forms.…”
Section: Methodsmentioning
confidence: 99%
“…Nucleotidases have some crystallographic structures deposited in the Protein Data Bank (PDB), distributed among several organisms: Thermotoga maritima ( Tm SurE): PDB ID's 1ILV, 1J9J, 1J9L, and 1J9K; Thermus thermophilus ( Tt SurE): PDB ID's 2E69, 2E6B, 2E6C, 2E6E, 2E6G, and 2E6H; Pyrobaculum aerophilum ( Pa SurE): PDB ID 1L5X; Aquifex aeolicus ( Aa SurE): PDB ID 2WQK; Salmonella typhimurium ( St SurE): PDB ID's 2V4N, 2V4O, 4G9O, and 4GAD, and Coxiella burnetii ( Cb SurE): PDB ID 3TY2 . Recently, our group reported the crystallization of Xf SurE and preliminary X‐ray crystallographic analyses . Two crystal forms were obtained; both belong to space group C 2, but with different number of monomers in the asymmetric unit …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations